ANALYSIS OF THE EFFECT OF REGIONAL ORIGINAL INCOME ON DEVELOPMENT OF DEVELOPMENT BY CAPITAL EXPENDITURE AS A MODERATING VARIABLE IN ACEH, NORTH SUMATERA, RIAU AND WEST SUMATERA PROVINCES 2010-2017 - Padang, Novi Natalia (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study was to analyse the effect of local revenue on development developments with capital expenditure as moderating variables in the provinces of Aceh, North Sumatra, Riau and West Sumatra. The population of this study were Aceh Province, North Sumatra, Riau and West Sumatra in 2010 to 2017. Observation samples were selected using saturated sample methods. Data was processed using panel data regression statistical test methods. The results of this study prove that based on regional tax, regional levies, the results of separated regional wealth, and other legitimate Local Government Revenue (LGR) simultaneously, have a significant effect on Gross Regional Domestic Products (GRDP) variables. Based on the results of the moderation test with interaction test, capital expenditure has a significant effect in moderating the effect of regional taxes, regional retribution, separated regional wealth results, other Local Government Revenue (LGR) on Gross Regional Domestic Products (GRDP).